IMPLEMENTATION OF TOPSIS METHOD IN SUPPLIER SELECTION SYSTEM WITH RAPID APPLICATION DEVELOPMENT - Ikhwanda Buyung Mangunsong; Muhammad Dedi Irawan (IDEALIS : InDonEsiA journaL Information System, 2025)
Technology in creating web-based information systems is developing very quickly. The ease of accessing informationand communicating has had a major impact on industry, pushing it towards digital systems. CV. Berjaya Jaya Abadi, acontractor company which operates in the field of providing various types of paint, faces the challenge of selecting the bestsupplier among several alternatives so as to enable a system development process that is faster, iterative, and focuses on userneeds, resulting in optimal and efficient solutions. in supplier selection. This research aims to build and develop a system basedon previous research using Rapid Application Development (RAD). This research also updates the criteria and adds sub-criteriato maximize the effectiveness of the TOPSIS method in the supplier selection process. By adopting the TOPSIS system, companiescan make more effective, efficient and data-driven decisions, which ultimately helps improve competitiveness and performance.This system is designed to simplify decision making in selecting suppliers by considering six main criteria, namely Delivery,Performance History, Price, Quality, Loyalty and Service. This research shows that the system developed can provide supplierrankings based on predetermined criteria, so that it can help companies choose suppliers that best suit their needs. The researchresults show th